PRELIMINARY STUDY ON AQUACULLURE OF CTENOPHARYNGODON IDELLA VAL. - Al-Jawda, J. M.; Balasem, A. N.; Asmar, K. R.; Ali, A - S. K. (The Iraqi Journal of Veterinary Medicine, 2021)
The classical method of aquaculture in Iraq employed Cyprinus carpio L. (Common carp) as monoculture or as predominat species togather with grass carp and silver carp. In the present study monoculture of grass carp was performed. Three - hundreds fingerlings of grass carp of 1.5 g weight were cultured in about 600 m2 eartheen pond from 20th of June till 9th of November, 1997. For the first two months of the experiment, no additional feed was added to what had been available in the pond. For the rest of the culture period, 1773 kg of five species of plants were utilized. They were included 91 kg of Phargmites australis, 972 kg of Paspalim sp., 423 kg of Medicago sativa, 171 kg of Ceratophyllum demersum and 116 kg of Paspalum Paspaloides. In addition to that a total of 150 kg of manure was used as a fertilizer in three occasions. At the end of the experiment the average weight of the fishes was 498 gm ranged from 370 gm to 980 gm. Further study was commence where 300 fingerlings of grass carp weighting 34 gm as an average were cultured together with 50 fingerlings of silver carp (average weight 92 gm). The experiment January 1998. For the first two months of experiment the fishes didn’t consume began in additional food probably due to the low temperature of water during this period.